Model for conditional training of elite female volleyball players - Karabiberov, J. (Journal of Applied Sports Sciences, 2020)
The manuscript presents the model for conditional training implemented in 2018 in the new female volleyball national team. The methods of the Bulgarian training system Fit Motion-Professional were used with a female national team for the first time. The training scheme follows the modular principle and is based on innovative methods and principles, various means and parallel-consecutive planning aimed mostly at the development of the motor qualities in each module. The interrelations between the basic motor qualities have been surveyed as well as the dynamics in their development at the different stages and in the different modules, and their efficiency in the volleyball game. The major aim of this manuscript is to study the efficiency of the model for conditional training of elite female volleyball players. Some new equipment and facilities have been designed for functional-conditional training in relation to the team`s preparation. In order to prove the higher efficiency of the model compared to the standard conditioning training used in Bulgaria, an experiment was further carried out with the Republican Women`s Volleyball Champion, the team of Maritsa Plovdiv.